Influência do black carbon na temperatura do ar e umidade relativa do ar do Pantanal Mato-Grossense - Lima, André Matheus de Souza (2024)
Understanding how Black Carbon (BC) affects the atmosphere and its consequences on meteorological variables, such as air temperature and relative humidity, is essential for evaluating variations in these variables in the face of projections involving global climate change. In this study, Mutual Information was used to verify the existing dependence between random variables, allowing the observation of whether there is a certain sensitivity of air temperature and relative humidity to the presence of BC particles in the region, based on data collected at the Pantanal Advanced Research Base of UFMT between 2017 and 2019. The results demonstrate the increase in BC concentrations directly impacting air temperature and relative humidity, as well as their atmospheric interactions. These increases are evidenced through Kruskall-Wallis and Dunn tests, to verify the differences between the four variables used in this study, and the Dunn test for the comparison of the three years studied. The accumulation of BC particles leads to a process responsible for warming the surrounding air, resulting in difficulties for species adapted to humid environments. During the dry season in the region, characterized by low precipitation levels, atmospheric conditions worsen, intensifying due to recurrent anthropogenic actions over the three years studied. Both air temperature and relative humidity showed higher sensitivity to these conditions. Therefore, changes in air temperature and relative humidity cannot be neglected and should be analyzed, as their alterations can directly affect the Pantanal biome.